TRANSFORMASI KEUANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) MELALUI PENERAPAN AKUNTANSI SEDERHANA - Jasiyah, Rabiyatul; Rusmardiana, Ana; Bakri, Asri Ady; Junaid, Asriyani (Jurnal Pengabdian Masyarakat Sabangka, 2024)
This Community Service aims to increase the knowledge and skills of business actors in the application of simple accounting, facilitate MSME actors in preparing accurate and easy-to-understand financial reports, and provide solutions for MSMEs to more easily access financing through better financial records. The method used in this activity is to identify and select participants, carry out socialization, education and mentoring, conduct monitoring, evaluation and assessment. This seminar was attended by 20 MSME players. The results of this service show an increase in the knowledge and skills of MSME actors in Mandai District, Maros Regency in the application of simple accounting, especially regularity in financial records, making financial reports so that it makes it easier for MSME actors to obtain access to financing. This service helps MSMEs in monitoring financial conditions and increasing their competitiveness and business continuity.